(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Ficus microcarpa Linn. (Syn: Ficus nitidas; Family: Moraceae) grows in Tropical and Subtropical regions of India, used for variety of purpose in traditional medicine. The usefulness of this plant is described in many folk books including Ayurveda and different biologically active phytoconstituents were isolated from plant. But no reports are available on morph anatomy, and phytochemical studies, hence present attempt was undertaken to investigate the microscopically and preliminary phytochemical and Physico-chemical studies on the leaves of Ficus microcarpa. The study reveals the leaves are variable, coriaceous, oblong, elliptic to broadly elliptic or obovate. The transverse section of the leaves shows presence of epidermis, sponge parenchyma, bicollateral vascular bundles, nonglandular, glandular trichome and spiral vessels. The powder microscopy revealed the presence of anomocytic stomata, glandular trichome, covering trichome and prismatic calcium oxalate crystals. Physicochemical parameters like ash value, extractive value and phytochemical screening with different reagents showed the presence of fluorescence compounds, steroids, triterpenoids, phenols, tannins and flavonoids.